Habitat and Burrow System Characteristics of the Blind Mole Rat Spalax galili in an Area of Supposed Sympatric Speciation - Lövy, Matěj; Šklíba, Jan; Hrouzková, Ema; Dvořáková, Veronika; Nevo, Eviatar; Šumbera, Radim (PloS one, 2015)
A costly search for food in subterranean rodents resulted in various adaptations improving their foraging success under given ecological conditions. In Spalax ehrenbergi superspecies, adaptations to local ecological conditions can promote speciation, which was recently supposed to occur even in sympatry at sites where two soil types of contrasting characteristics abut each other. Quantitative description of ecological conditions in such a site has been, nevertheless, missing. We measured characteristics of food supply and soil within 16 home ranges of blind mole rats Spalax galili in an area subdivided into two parts formed by basaltic soil and pale rendzina. We also mapped nine complete mole rat burrow systems to compare burrowing patterns between the soil types. Basaltic soil had a higher food supply and was harder than rendzina even under higher moisture content and lower bulk density. Population density of mole rats was five-times lower in rendzina, possibly due to the lower food supply and higher cover of Sarcopoterium shrubs which seem to be avoided by mole rats. A combination of food supply and soil parameters probably influences burrowing patterns resulting in shorter and more complex burrow systems in basaltic soil.
Keywords: Genetic Speciation; fyziologická adaptace; Spalax; Ecosystem; Behavior, Animal; sympatrie; Animals; půda; vznik druhů (genetika); chování zvířat; Soil; Sympatry; zvířata; ekosystém; Adaptation, Physiological